Internet Activism in Asia-Pacific: A Comparative, Cultural History - Goggin, Gerard; McLelland, Mark; Lee, Kwangsuk; Frances, Shaw; Tkach-‐Kawasaki, Leslie; Tamura, Takanori; Yu, Haiqing (AoIR Selected Papers of Internet Research, 2013)
As the internet has become a central delivery platform across contemporary mediascapes, activism around internet access, freedom, censorship, and openness has become more prominent. As internet freedom gathers momentum as a global media policy concept and movement, it is important to interrogate the terms in which it is constructed and understood. All too often, and certainly evident in these recent moves, is a strong, normative sense in which North American concepts of internet, media, activism and even ‘freedom’ shape the boundaries and modes of contemporary debates, policy frameworks, and action. Against this backdrop, this paper seeks to reframe contemporary notions of internet freedom, their politics, publics, actors, and movements. Drawing from the wider project on Asia-Pacific internet histories, this paper presents three case studies of internet activism –– respectively in Australia, South Korea, and Japan.